2017
DOI: 10.1177/1352458517717807
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal functional connectivity of thalamic sub-regions contributes to fatigue in multiple sclerosis

Abstract: Regional thalamic RS FC abnormalities with different cortical regions, including the frontal lobe, sensorimotor network, precuneus, insular cortices, and cerebellum contribute to fatigue in MS. Abnormal RS FC of selected thalamo-cortical connections explains different components of fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 35 publications
10
54
0
Order By: Relevance
“…Neuroimaging studies (60,81,82) demonstrated that the main pathogenic substrate of MS-related fatigue could be a dysfunction of the circuits between the thalamus, the basal ganglia, and the cortex, and neurophysiological findings support this hypothesis. Indeed single-pulse TMS studies demonstrated that in MS patients the pathogenesis of fatigue is not driven by mechanisms directly related to corticospinal functioning but is due to alterations in structures located upstream to the primary motor cortex (39).…”
Section: Neurophysiology As Investigating Tool For the Pathogenic Mecmentioning
confidence: 91%
“…Neuroimaging studies (60,81,82) demonstrated that the main pathogenic substrate of MS-related fatigue could be a dysfunction of the circuits between the thalamus, the basal ganglia, and the cortex, and neurophysiological findings support this hypothesis. Indeed single-pulse TMS studies demonstrated that in MS patients the pathogenesis of fatigue is not driven by mechanisms directly related to corticospinal functioning but is due to alterations in structures located upstream to the primary motor cortex (39).…”
Section: Neurophysiology As Investigating Tool For the Pathogenic Mecmentioning
confidence: 91%
“…The second strategy associates FC values of MS patients with clinical data, such as cognitive ( 50 ) and motor performance ( 67 ), fatigue ( 40 , 68 , 69 ), depression ( 70 ), or sleep disturbance ( 71 ). Here, either the respective symptom severity is used as a regressor of the FC data or the group of MS patients is subdivided into subgroups of preserved vs. impaired function.…”
Section: Overview Of Selected Literaturementioning
confidence: 99%
“…Over the last twenty years, an increasing number of studies have evaluated the pathogenetic bases of MS-related fatigue. Converging evidence from neurophysiology 7,8 and neuroimaging 9,10 demonstrated that, in patients with MS, fatigue has a central origin and a dysfunction of the circuits between thalamus, basal ganglia and cortex could be its main pathogenic substrate. Initially, many authors focused on areas of possible interest for motor fatigue (cortex and basal ganglia), that were easy to investigate with neuroimaging and neurophysiological tools.…”
Section: And Thementioning
confidence: 99%